PENGARUH DOSIS INOKULUM AZOLLA DAN PUPUK KALIUM ORGANIK TERHADAP KETERSEDIAAN K DAN HASIL PADI PADA ALFISOL JUMANTONO - Ransa Gustrada Syarif; Hery Widijanto; Sumarno Sumarno (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2013)
Title : The Effect of Azolla Inoculum Dosage and Organic Potassium Fertilizer on Potassium Availability and Rice Yield in Alfisol. This research conducted to determine the proper dose of azolla inoculum and organic potassium to increase the availability of potassium and increase yield of paddy rice,and to determine the best dose combination instead K availability. The research was conducted in May 2012 until November 2012 at Jumantono dryland research centre, Karanganyar regency and Chemical and Soil Fertility laboratory Agriculture Faculty UNS Solo. The research used Completely Randomized Design (CRD) using P as the treatment combination of Azolla inoculum and organic pottasium. For comparison is the treatment of manure and NPK fertilizer. The Variabel for this research are pottasium exchanged, CEC, organic matter, total N in the soil, dry weight of grain harvested and milled, and weight of 100 seeds. Data were analyzed by F test and DMRT at 5% level. The results showed that the combination dose of Azolla inoculum and organic potassium can increase the availability of potassium and rice yields on Alfisol soil. The research showed P8 (Combination of azolla inoculums 5 ton/ha and organic potassium 100 kg/ha) as the highest treatment.